PENGARUH PENGETAHUAN PRODUK TERHADAP NIAT BELI DENGAN SIKAP SEBAGAI VARIABEL INTERVENING - DWI KUSUMA, IRMA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The increase of smartphone competition makes producer more intensive to provide the information about their products. It is done to improve consumer’s product knowledge so that it can lead to a positive attitude, where it can growing consumer’s purchase intention. This study aims to analyze and discuss the influence of product knowledge toward purchase intention with attitudes as an intervening variable. This research is a conclusive causal. The respondents in this study were visitors of WTC Surabaya. Samples taken are 110 people by using purposive sampling technique. The research instrument used was a questionnaire, the data obtained were processed by analysis of path (path analysis). The result shows that the relationship between each variable is significantly positive, and the mediation is proved partially. Keywords: product knowledge, purchase intention, and attitudes.